Enhanced performance of ilmenite modified by CeO2, ZrO2, NiO, and Mn2O3 as oxygen carriers in chemical looping combustion. (1st June 2017) - Sun, Zhenkun; Lu, Dennis Y.; Ridha, Firas N.; Hughes, Robin W.; Filippou, Dimitrios
Graphical abstract: Highlights: Ilmenite ore as oxygen carriers was modified by various guest metal oxides. The addition of NiO and Mn2 O3 accelerated reactivity of ilmenite towards CH4 . The addition of NiO and Mn2 O3 to ilmenite resulted in increased OTC s. The addition of CeO2 and ZrO2 improved the reactivity of ilmenites at 750 °C. The resistance to agglomeration was enhanced by the addition of guest metal oxides. Abstract: In this paper, Canadian ilmenite ore-based oxygen carriers (OCs) were, for the first time, prepared by coating the ilmenite ore particles with metal oxides of CeO2, ZrO2, NiO, or Mn2 O3 by using precursors of Ce(NO3 )3, Zr(O-t-Bu)4, Ni(NO3 )2 or Mn(NO3 )2, respectively. The reduction reactivity of OCs with methane was examined by temperature-programmed methane reduction (CH4 -TPR), and their cyclic performance during the chemical looping methane combustion was investigated isothermally in a thermogravimetric analyzer (TGA). It was demonstrated that the addition of all types of these metal oxides had a positive effect, such as an accelerated reactivity towards methane reduction and enhanced resistance to agglomeration. Specifically, the modification using CeO2 and ZrO2 improved the reactivity of ilmenites towards CH4 reduction at a lower temperature of 750 °C. However, the promotion effect decreased when the temperature was elevated to 800 °C. NiO modification not only enabled the ilmenite to improve reaction with CH4 due to the generation of a more active compound NiFe2 O4, but also to result in higher oxygen transport capacity. Similarly, Mn2 O3 modification showed a higher reactivity and a fast reaction rate towards the oxidation of CH4 attributed to the generation of ferrimanganic oxides. Furthermore, the overall oxygen transport capacity of Mn2 O3 composed OCs was increased caused by the variable valence of Mn. The addition of CeO2, ZrO2, and NiO always retarded the activation process of ilmenite ore, by contrast, Mn2 O3 modified samples accelerated the activation due to the irreversible phase transformation from Mn2 O3 to Mn3 O4 accompanied by a volume shrinking that led to a flawed particle surface reducing the diffusion resistance.